RESILIENCE OF THE INSTITUTION OF MARRIAGE IN FACING DOMESTIC PROBLEMS IN A LEGAL PERSPECTIVE: Maya Aufa UIN SMH Banten - maya aufa (Islamic Civil Law Departement of Shari'a Faculty at Islamic State University of Sultan Maulana Hasanuddin Banten, 2023)
The institution of marriage is a noble institution and has an honorable position in Islamic law and Indonesian national law. This is evidenced by the existence of special regulations related to marriage, namely Law Number 16 of 2019 concerning Marriage. Problems in domestic life will always be faced by every couple, the existence of the marriage institution is a benchmark for how husband and wife are able to face and get solutions to the problems faced, so that the integrity of the household is maintained. This paper aims to explain how the resilience of the marriage institution in an effort to find solutions to problems and conflicts in the household, so that family integrity remains harmonious. Based on qualitative descriptive research methods and analytical descriptive sociological normative approaches, it is concluded that: 1) It is necessary to understand the community about family resilience so that each individual couple understands the concept and purpose of marriage. (2). Optimizing BP4 institutions in bridging the resolution of household conflicts. (3) Strengthening family joints from various aspects, both economic and social and others, in order to minimize the divorce rate.